Representativeness of the Value Based Activities and Reports under the Dominating Influence of Counterparties - Gareev, B. R.; Zaikin, A. A. (International Journal of Economics and Financial Issues, 2016)
In the article the problems of the value based financial activities and reports in conditions of the economic entity dependence on suppliers and customers are being researched, the algorithms of calculation relevant in the meaning of the supplier and customer interests the indexes of economic profit are being developed, the forms of financial reporting and registers, forming the price-oriented financial indexes are being represented for the readers attention. Keywords: value based activities, financial reports, forms of economic influence, economic profit, relevant costs, opportunity costs. JEL Classifications: O150; E660; R130